The feet construction of 9-year-old children - Beata Szczepanoska-Wołowiec; Paulina Sztandera (Kazimierz Wielki University, 2018)
Introduction and purpose of the work, The human foot it is a very complex structure of the body, as it contains 26 bones, 19 muscles and 33 joints. Because of the cooperation all of those elements, the foot could fulfillthree basic functions such as load, amortization and locomotive functions. The aim of this research was to evaluate the feet construction in 9-year-old children from Masłów and Górno District. Material and method, The study involved 168 9-year-old children. There were 89 (53%) and boys 79 (47%) in the study group. The study was conducted in 2015/2016. The children were examined in schools after prior permission given by principals and parents or legal guardians. The body weight of the children was measured using the Tanita device and the body height was measured with the use of SECA. Then, the BMI index was calculated and compared to Centil grid presented in Olaf study. The plantar part of the foot was evaluated by 2D podoscanner. The relationship between the chosen parameters, sex and BMI was calculated. To examine the relationships, the author took advantage of nonparametric tests - Spearman's rank correlation analysis, Manna-Whitneya-Wilcoxona test and χ2 test. When the level of statistical significance equaled p